Social complexity in the third millennium cal BC in southern Portugal - Soares, Joaquina (2018)
The starting point of this paper is the extensive archaeological fieldwork developed at the Chalcolithic fortification of Porto das Carretas on the left bank of the Middle Guadiana River (Soares, 2013). The well-preserved stratigraphy and correlated radiocarbon dates of Porto das Carretas enabled a new and deep insight into the third millennium cal BC, displaying environmental, economic and social transformations from the first to the second half of the millenium. Furhermore, the integration of the local scale into the regional, and supra-regional levels of interaction have created a key framework for the construction of a dynamic model of increasing social complexity (Fig. 1). Thus, a proposal of a complex tribal organization of stable communities, during the first half of the third millennium cal BC is presented. They shared a kinship structure inherited from the megalithic societies and an economy based on intensive agriculture (cart, plow). This model of social organization began to collapse in the third quarter of the same millennium, mostly as a probable result of the development of craft specialisation, mainly metallurgy (copper-arsenic alloys). The control of metallurgy integrated in the European exchange network of prestige goods (Bell Beaker package) gave the elites a new source to amass significant wealth for their own immediate benefit, and also coercive power to impose an unequal and very hierarchical social structure similar to chiefdom.